Antarctic bioprospecting: in pursuit of microorganisms producing new antimicrobials and enzymes - Danilovich, Mariana Elizabeth; Sanchez, Leandro Arturo; Acosta, Federico Francisco; Delgado, Osvaldo Daniel (Polar Biology)
Intensive efforts are being made to find new compounds with antimicrobial activity. The search for these novel bio-products in sparsely explored environments may be the key to providing solutions for many emerging problems. Antarctic environments are valuable locations for bioprospecting. In this study, 63 cold-adapted bacterial strains of 6100 different colony morphotypes were isolated from Antarctic seawater samples around South Shetland and Deception islands. Strains were selected based on cold-active antimicrobial production and were grouped into 11 operational taxonomic units by internal spacer region-PCR and amplified ribosomal DNA restriction analysis. Isolates arbitrarily named 2D, 5D, and 6D were closely related to Halomonas titanicae, with 99.8, 98.9, and 96.7% identity according to 16S rDNA sequencing, and 99.7, 99.3, and 98.3% according to gyrB region sequence analysis, respectively. The isolate 18SH was closely related to Candida sake (99.2%) based on sequence analysis of the ITS1?5.8S rDNA?ITS2 and D1/D2 domain of 26S rDNA. Antimicrobials produced by isolates 2D, 5D, and 6D exhibited a low-molecular weight (< 6000 Da) and stability in wide pH and temperature ranges. When tested against foodborne and phytopathogenic bacteria, selected isolates exhibited a wide spectrum of activity. This work reports the isolation and identification of cold-adapted microorganisms with the ability to produce antimicrobial compounds with potential application in the pharmaceutical or in cold-chain management in the food industry. The current results highlight the potential of the Antarctic environment as a valuable and underexploited source of new antimicrobial molecules with exceptional properties for different biotechnological applications. Fil: Danilovich, Mariana Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Sanchez, Leandro Arturo. Consejo Nacional de ...